European Landmarks regarding the Citizenship - S.G. Barbu; D.A. Cerbu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
At the European Union level, several regulations concerning European citizenship are briefly examined in this paper. Furthermore, the study delves into the institution of citizenship as reflected in the Constitutions of various member states, including Romania, focusing on its general aspects within the framework of constitutional law. Particular attention is given to the evolution of citizenship rights and obligations, both at a national and EU level, highlighting the intersection of national sovereignty and transnational governance. The analysis also explores the implications of these regulations for individual rights, political participation, and the legal status of citizens within the broader European context.